Hubungan Peer Conformity terhadap Impulse Buying dengan Fear of Missing Out (FoMO) Sebagai Variabel Mediasi pada Gen Z Pengguna Paylater di Indonesia - Muhammad Hisyam Ramadhan; Miftahun Najah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study aims to examine the effect of peer conformity on impulse buying with Fear of Missing Out (FoMO) as a mediating variable among Generation Z users of paylater services in Indonesia. A quantitative correlational design was employed involving 167 respondents selected through purposive sampling. Data were collected using a Likert scale questionnaire and analyzed using linear regression and mediation analysis. The results show that peer conformity has a significant positive effect on FoMO (β = 0.488; p < 0.01) and on impulse buying (β = 0.337; p < 0.01). In addition, FoMO has a significant positive effect on impulse buying (β = 0.223; p < 0.01). The mediation analysis indicates that FoMO acts as a partial mediator in the relationship between peer conformity and impulse buying, with a total effect of β = 0.446 (p < 0.01). These findings suggest that impulse buying behavior among Generation Z is influenced not only directly by social pressure but also indirectly through a cognitive appraisal process that generates FoMO as an emotional mediator. This study contributes to consumer psychology literature and provides practical implications for managing consumptive behavior in the digital era.